RUMAH KACA’s Minke’s Death and Its Question on Postcolonial Catastrophe - Gabriel Fajar Sasmita Aji (Journal of Language and Literature, 2023)
Rumah Kaca, or House of Glass, is the last episode of Pramoedya’s Tetralogy of Buru, and it gives “a surprise,” or a shocking end of Minke’s postcolonial strives. Here, he died several days after his coming home from exile. This looks surely to present the catastrophe of the native’s postcolonial hope and dream. The strategy of the colonial government in conducting “house of glass” has gone successful and Minke’s death might stop any local political activities opposing the government. However, this phenomenon, i.e. the death of Minke, appears as the new perspective dealing with the local Indonesians, or pribumi, in undergoing postcoloniality. Minke’s death is not to stop his postcolonialism, since he’s still kept it in his writings. Those are to represent Minke’s continuation in flaming postcoloniality to the next local postcolonialists.  The novel Rumah Kaca seems to reemphasize the idea of postcolonialism, previously stated in the first episode, Bumi Manusia, that the main weapon of postcolonialism is the postcolonial brain of the postcolonialists. As the concepts of postcolonial ideologies by Bill Ashcroft and Annia Loomba, this discussion focuses on how Indonesian postcolonialism, by Pramoedya’s Tetralogy of Buru, has the ultimate power in writings, since compared to the colonial government the colonized’s technological civilization is much less powerful. In other words, Minke’s death does not mean the end of the local postcoloniality, and it is a new perspective in dealing with the common concept.